Свічники Михайла Китриша - Ликова, О.Г. (Сіверщина в історії України, 2021)
У Національному музеї-заповіднику українського гончарства в Опішному зберігається найбільша персональна колекція кераміки Михайла Китриша в Україні. У ній представлено понад п’ятдесят свічників майстра. Поважна колекція свічників є й у приватному зібранні кераміки самого гончаря. Авторкою публікації зроблено аналіз цього виду виробів опішненського майстра. З’ясовано місце свічників у виставковій історії Михайла Китриша. Простежено період їх виготовлення. За формотворчими ознаками виділено основні типи свічників. Окреслено основні елементи декору. Акцентовано увагу на питанні атрибутування свічників опішненського гончаря. Candlesticks have been around for a long time, but in modern life they are no longer used for their intended purpose. Traditional clay candlestick is not only a handy place for a candle. It also performs a decorative function. This studio characterized candlesticks, which were produced by Opishne’s potter Mykhailo Kytrysh. Analysis was carried out on the basis of a personal collection of the potter at the National Museum of Ukrainian Ceramics in Opishne and private collection of the master, which is stored in his home. Mykhailo Kytrysh produced clay candlesticks constantly. But information about this was very rare in published literature. The first information about his candlesticks was published in the publication in 1999. Catalogs of exhibitions, which actively participated in the potter from 1970, became a separate source, which includes candlesticks by Mykhailo Kytrysh. Mykhailo Kytrysh’s works have their own characteristic features. They are different in both decorative and formative elements. The candlesticks of Mykhailo Kytrysh are obligatory and have a container for a candles and a saucers for draining wax. The number of candles varied from one to nine. This element is often combined with decorative elements in the form of animals and devils. Often they are decorated with colored glazes. Dark glazes used rarely. The period of the production of candlesticks by Mykhailo Kytrysh is dated 1972-2010. Almost all of them are fully attributed. The oldest candlestick, on which the ritual is marked with the year of manufacture, is dated 1989 and is kept in the private collection of Mykhailo Kytrysh. Candlesticks of large size (up to one meter in diameter) potter made since 1997, when he became a participant of the First Regional Symposium “Pottery Train on Maidens and Parks of Ukraine” in Opishne. Kytrysh’s candlesticks were a rarity at the exhibitions. They often presented sculptural dishes, vases for the dishes and plates.